Maze Solver Robot - Majdy Sabra; Naser Tayeh (My University, 2024)
In the last five decades, cutting-edge robotic technology has become indispensable across various industries, delivering unparalleled precision in tasks spanning industrial production, healthcare, transportation, and security. Nevertheless, specialized robots tailored to specific functions often demand intricate technical support and incur substantial maintenance costs. This project unveils a highly adaptable maze-solving robot, equipped with three Ultra Sonic sensors, three Sharp IR sensors, 4 micro switches , a module IR sensor to detect end of maze , an LCD for measurement, two DC motors, an Arduino Mega, and a motor driver.This robot is meticulously crafted to adeptly navigate complex 3D mazes. Collected data from an array of sensors is seamlessly transmitted to an Arduino micro controller [1], which takes charge of wheel movement direction after executing essential operations on the received information. The robot excels in traversing and conquering 3D mazes, guided by a fundamental principle: detecting its present location and making informed decisions for subsequent moves.This undertaking introduces a sophisticated three-wheeled robot featuring dual operational modes. Leveraging a singular Arduino Mega micro controller and an array of sensors, including Sharp IR, IR, and switches for hit detection, the robot exhibits versatile capabilities. Its primary objective remains the navigation of predetermined paths on flat surfaces, complemented by a dedicated emphasis on obstacle avoidance.